2022
DOI: 10.1002/jev2.12240
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of MSC‐derived apoptotic vesicles identifies Fas inheritance to ameliorate haemophilia a via activating platelet functions

Abstract: Apoptotic vesicles (apoVs) are apoptotic cell‐derived nanosized vesicles that play a crucial role in multiple pathophysiological settings. However, their detailed characteristics, specific surface markers, and biological properties are not fully elucidated. In this study, we compared mesenchymal stem cell (MSC)‐derived apoVs and exosomes from three different types of MSCs including human bone marrow MSCs (hBMSCs), human adipose MSCs (hASCs), and mouse bone marrow MSCs (mBMSCs). We established a unique protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(98 citation statements)
references
References 76 publications
2
96
0
Order By: Relevance
“…The preparation of ApoBDs from MSCs usually includes the induction of apoptosis with staurosporine doses of 250 nM–0.5 μM for 12 h, followed by centrifugation at 800–1000 g to remove cell debris and then at 16000 g to precipitate the ApoBDs [ 108 , 109 , 113 ]. 200 μM H 2 O 2 for 8 h or nutrient deprivation by culturing MSCs in PBS for 24 h are also used as inducers of cell death in MSCs [ 112 ]. Le et al [ 114 ] suggested using high hydrostatic pressure at 50 MPa for 36 h to induce MSC apoptosis ex vivo.…”
Section: Methods Of the Msc-derived Apobds Isolationmentioning
confidence: 99%
See 3 more Smart Citations
“…The preparation of ApoBDs from MSCs usually includes the induction of apoptosis with staurosporine doses of 250 nM–0.5 μM for 12 h, followed by centrifugation at 800–1000 g to remove cell debris and then at 16000 g to precipitate the ApoBDs [ 108 , 109 , 113 ]. 200 μM H 2 O 2 for 8 h or nutrient deprivation by culturing MSCs in PBS for 24 h are also used as inducers of cell death in MSCs [ 112 ]. Le et al [ 114 ] suggested using high hydrostatic pressure at 50 MPa for 36 h to induce MSC apoptosis ex vivo.…”
Section: Methods Of the Msc-derived Apobds Isolationmentioning
confidence: 99%
“…In recent work, Zhang et al [ 112 ] compared the proteomic profiles of ApoBDs and exosomes derived from three different types of MSCs, including human BM-MSCs, human AD-MSCs, and mouse BM-MSCs and showed that ApoBD protein patterns are 80% matched between BM-MSCs and AD-MSCs. More functional proteins were present in ApoBDs compared to exosomes obtained from the same cells.…”
Section: Msc-derived Extracellular Vesicles: Exosomes Microvesicles A...mentioning
confidence: 99%
See 2 more Smart Citations
“…ApoVs are derived from various types of cells, such as precursor cells, endothelial cells, immunocytes, and mesenchymal stem cells (MSCs) [ 19 ]. The buoyant density of ApoVs ranges from 1.118 to 1.228 g/mL, making them denser than sEVs (1.05–1.15 g/mL) and MVs (1.03–1.10 g/mL) [ 20 , 21 ]. Until now, the classification of ApoVs has been a matter of debate.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%